Engineering Education with Tool Based Technical Activity (TBTA) - Dineshkumar, R.; Kalimuthu, M.; Gopalakrishnan, S.; Deepika, K. (Journal of Engineering Education Transformations, 2022)
The main aim of Engineering education is to impart intellectual development and promote technical skills to engineering students. Teaching methodology plays a major role in the teaching-learning process. The basic goal of engineering students is to nurture knowledge in the relevant areas. Engineering education is technology-oriented; the learners should apply his/her knowledge to a specific application. To develop their technical skills, the students should identify suitable learning styles for their potentialities. The proper teaching methodology is a key point to success in engineering education. The industry expects the students to be high-quality engineers and industry-ready after completing their courses. Due to lagging in technical training and syllabus provided by the university doesn’t match with the real- time industry projects. To achieve these outcomes technical-based activity needs to be enhanced in engineering education. In this paper, we proposed a Tool Based Technical Activity (TBTA) teaching method that converges traditional teaching methods which improve the student’s attention in learning. Students’ feedback with TBTA improves students’ learning, communication, technical skills, and knowledge.